2013
DOI: 10.5144/0256-4947.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Saudi women’s acceptance and attitudes towards companion support during labor: Should we implement an antenatal awareness program?

Abstract: BACKGROUND AND OBJECTIVESDespite the known benefits of support during chilbirth, most hospitals in Saudi Arabia do not allow a companion during labor. This can be due to cultural beliefs among pregnant Saudi women. The aims of this study are to describe Saudi women’s preferences towards supportive companions during labor and to explore their attitudes and knowledge about the importance of support during childbirth.DESIGN AND SETTINGProspective cohort study conducted in three governmental tertiary hospitals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…A study done at university college teaching hospital, Ibadan, Nigeria reported that 75% of the respondents desired companionship in labour [12]. Another study in Saudi Arabia found that 59% of women had support during labour [18]. In index study, most women preferred their husband as labour companion (47.25%); this however contrasts with study by Bakhata et al [12] where 68% of women declined to have male partners present during labour.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…A study done at university college teaching hospital, Ibadan, Nigeria reported that 75% of the respondents desired companionship in labour [12]. Another study in Saudi Arabia found that 59% of women had support during labour [18]. In index study, most women preferred their husband as labour companion (47.25%); this however contrasts with study by Bakhata et al [12] where 68% of women declined to have male partners present during labour.…”
Section: Discussionmentioning
confidence: 77%
“…Evidence indicates that continuous support during labour has a number of measurable positive impacts on key birth outcomes [12]- [19]. It has been found to significantly reduce the number of caesarean sections and operative vaginal deliveries, an increase in the number of normal births, a reduction in the use of analgesia and a reduction in labour duration [18] [19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations